INNOVATIVE METHODS FOR DEVELOPING FUTURE YOUNG OFFICERS' SOFT SKILLS: PRINCIPLES OF THE "BEST COMMANDER" CORRECTIONAL PROGRAM (Web of Teachers: Inderscience Research, 2025)
In modern military education, the development of soft skills is as crucial as technical and tactical training. This study explores innovative methods for enhancing the soft skills of future young officers through the "Best Commander" correctional program. The program is designed to improve leadership, communication, problem-solving, teamwork, and decision-making abilities by integrating interactive learning strategies, scenario-based exercises, and real-time feedback mechanisms. The research highlights the importance of adaptive learning environments, where cadets develop critical thinking and emotional intelligence to effectively navigate complex military operations. The findings suggest that applying modern pedagogical technologies in military training can significantly enhance officers' readiness, leadership effectiveness, and strategic decision-making skills.